Methylation of glucocorticoid receptor gene promoter modulates morphine dependence and accompanied hypothalamus–pituitary–adrenal axis dysfunction. Issue 7 (12th September 2016) - Zhu, Jie; Zhu, Feng; Zhao, Na; Mu, Xin; Li, Pingping; Wang, Wei; Liu, Jian; Ma, Xiancang
Abstract : Previous studies demonstrated that dysfunction of the hypothalamus–pituitary–adrenal (HPA) axis played an important role in morphine dependence. Nonetheless, the molecular mechanism underlying morphine‐induced HPA axis dysfunction and morphine dependence remains unclear. In the current study, 5′‐aza‐2′‐deoxycytidine (5‐aza), an inhibitor of DNA methyltransferases (DNMTs), was used to examine the effects of glucocorticoid receptor (GR) promoter 17 methylation on chronic morphine–induced HPA axis dysfunction and behavioral changes in rats and the underlying mechanism. Our results showed that chronic but not acute morphine downregulated the expression of nuclear GR protein and GR exon 17 variant mRNA, and upregulated the methylation of GR 17 exon promoter in the hippocampus of rats. Meanwhile, 5‐aza per se had no effect on observed molecular and behavior change. In contrast, pretreatment of 5‐aza into rat hippocampus reversed chronic morphine–induced hypermethylation of GR 17 promoter and decrease in GR expression. Moreover, pretreatment of 5‐aza attenuated chronic morphine‐enhanced HPA axis reactivity and the naloxone‐precipitated somatic signs in morphine‐dependent rats. Our results suggest that chronic morphine induced hypermethylation of GR 17 promoter, which then downregulated the expression of hippocampal GR, and was thus involved in chronic morphine–induced dysfunction of the HPA axis and the modulation of morphine dependence. Moreover, chronic morphine–induced hypermethylation of GR 17 promoter may be at least partially due to the increase in hippocampal DNMT 1 expression and its binding at GR 17 promoter in the rat hippocampus. © 2016 Wiley Periodicals, Inc. Abstract : Chronic morphine induced hypermethylation of GR 17 promoter via increasing hippocampal DNMT1 expression and its binding at GR 17 promoter, which then downregulated the expression of hippocampal GR, and was thus involved in morphine‐induced hyperreactivity of the HPA axis and morphine dependence. MBD2 may also contribute to downregulation of GR 17 mRNA.